Coronal mass ejection hits mercury: A.I.K.E.F. hybrid-code results compared to MESSENGER data. (April 2018) - Exner, W.; Heyner, D.; Liuzzo, L.; Motschmann, U.; Shiota, D.; Kusano, K.; Shibayama, T.
Abstract: Mercury is the closest orbiting planet around the sun and is therefore embedded in an intensive and highly varying solar wind. In-situ data from the MESSENGER spacecraft of the plasma environment near Mercury indicates that a coronal mass ejection (CME) passed the planet on 23 November 2011 over the span of the 12 h MESSENGER orbit. Slavin et al. (2014) derived the upstream parameters of the solar wind at the time of that orbit, and were able to explain the observed MESSENGER data in the cusp and magnetopause segments of MESSENGER's trajectory. These upstream parameters will be used for our first simulation run. We use the hybrid code A.I.K.E.F. which treats ions as individual particles and electrons as a mass-less fluid, to conduct hybrid simulations of Mercury's magnetospheric response to the impact of the CME on ion gyro time scales. Results from the simulation are in agreement with magnetic field measurements from the inner day-side magnetosphere and the bow-shock region. However, at the planet's nightside, Mercury's plasma environment seemed to be governed by different solar wind conditions, in conclusion, Mercury's interaction with the CME is not sufficiently describable by only one set of upstream parameters. Therefore, to simulate the magnetospheric response while MESSENGER was located in the tail region, we use parameters obtained from the MHD solar wind simulation code SUSANOO (Shiota et al. (2014)) for our second simulation run. The parameters of the SUSANOO model achieve a good agreement of the data concerning the plasma tail crossing and the night-side approach to Mercury. However, the polar and closest approach are hardly described by both upstream parameters, namely, neither upstream dataset is able to reproduce the MESSENGER crossing of Mercury's magnetospheric cusp. We conclude that the respective CME was too variable on the timescale of the MESSENGER orbit to be described by only two sets of upstream conditions. Our results suggest locally strong and highly variable dynamics of the CME on timescales of 15 min while MESSENGER was near closest approach. Highlights: Approximation of CME with two upstream conditions (SL-case, SU-case) is possible. SL-case: Agreement with bow-shock and day-side magnetosphere measurements. SU-case: Agreement with tail-crossing and night-side measurements. None of the SL- and SU-cases are able to reproduce the cusp and cusp filaments. CME variability is concluded to be of 15 min to explain cusp measurements.